Barriers and facilitators of sports in Dutch Paralympic athletes: An explorative study - Jaarsma, E. A.; Geertzen, J. H. B.; de Jong, R.; Dijkstra, P. U.; Dekker, R. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of this study was to gain insight in barriers and facilitators of sports in paralympic athletes. An online questionnaire was distributed through the Netherlands Olympic Committee and National Sports Confederation to determine personal and environmental barriers and facilitators of sports participation. The International Classification of Functioning, Disability and Health model and theory of planned behavior were used to respectively categorize the results in environmental and personal factors, and attitude, subjective norm and perceived behavioral control. Seventy-six Dutch Paralympic athletes completed the questionnaire (51% response rate). Barriers and facilitators experienced by ambulant and wheelchair athletes were compared. Most frequently mentioned personal barrier was dependency of others (22%), while most frequently mentioned environmental barrier was lack of sports facilities (30%). Wheelchair athletes mentioned more barriers (median = 3, interquartile range: 0.5-6), than ambulant athletes (median = 1.0,interquartile range:0.0-3.0, P = 0.023). One-third of the athletes did not experience any barriers. Most frequently mentioned personal facilitators to initiate sports participation were fun (78%), health (61%), and competition (53%). Most frequently mentioned environmental facilitator was social support (40%). This study indicated that barriers of sport were mostly environmental, while facilitators were usually personal factors. Attitude and subjective norm were considered the most important components for intention to participation in sports. The facilitators outweighed the barriers and kept the athletes being active in sports.